Sosialisasi Penerapan Budaya 3S (Senyum, Salam dan Sapa) Para Siswa di SMA Yaniic Jakarta Utara - Sonya Sidjabat; Indriyati Indriyati; Sulistya Pribadi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
As a lecturer, you are required to the three dharma of higher education. One of them is community Service (PkM). On this occasion we will hold a PkM at SMA YANIIC, North Jakarta which is located at JlTeluk Semangka No 103 Komp. BPP Sukapura Kec. Cilincing. School as educational institutions also need to develop a culture that is friendly to their customers namely students and stakeholders. Thuscreating conditions for effective teaching and learning activities because based on pleasant and friendly feelings among all academics and school staff and management. Based on this, we strive to provide training on the most important services namely, Smile, Regards and Greetings(3S) to improve the application of Smile, Regards and Greetings(3S) culture in the school environment. It is hoped that through this training, the teachers and the students will be able to provide Smile, Regards and Greetings which are the most important services. So that learning and teaching activities are expected to be fun.